Estudio de factibilidad para la creación de una tienda mixta "pa' eso estamos.com en la comuna 17 de la ciudad de Cali. - Sánchez Paja, Robinson; Torres Rodríguez, Leonardo (Universidad Antonio Nariño, 2024)
The development of the project consists of knowing the feasibility or not of an MIXTA store in the Valle del Lili sector in commune 17 of the city of Cali, for which in the first instance a study is carried out to establish strategies to take advantage of the sector market. Likewise, know the equipment and logistics necessary to launch the store. Likewise, determine the personnel required in the store and the financial analysis to determine its viability.